2022
DOI: 10.3389/fpsyt.2022.870128
|View full text |Cite
|
Sign up to set email alerts
|

Conspiratorial Beliefs About COVID-19 Pandemic - Can They Pose a Mental Health Risk? The Relationship Between Conspiracy Thinking and the Symptoms of Anxiety and Depression Among Adult Poles

Abstract: The aim of the study was to describe the relationship between the tendency to believe in false information about the COVID-19 pandemic, tendency to believe in conspiracy theories and the severity of anxiety and depression symptoms among the surveyed Poles. The study was conducted via the Internet in a group of 700 people aged 24.8 ± 6.3 years (mean ± SD). 585 females and 110 males were involved. Scales such as Generic Conspiracist Beliefs Scale (GCBS), Hospital Anxiety and Depression Scale (HADS) and the origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In this regard, many jobs were forced to close permanently or temporarily, and in other cases, the workers had to adapt their daily tasks. [ 18 ] When a vulnerable population such as that of migrants living in informal settlements lose their jobs, they have to cope with loss of income, food shortages, family worries, and uncertainty about their future, [ 19 , 20 ] and this worsening of socio-economic conditions together with the loss of employment for low-income individuals increases the risk of developing psychiatric disorders, [ 21 ] such as psychological distress, depressive disorders, anxiety disorders, and substance use disorders. [ 22 ] Psychological distress refers to a range of nonspecific symptoms of stress, anxiety and depression that can trigger and act as signs of common mental disorders, such as depressive and anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, many jobs were forced to close permanently or temporarily, and in other cases, the workers had to adapt their daily tasks. [ 18 ] When a vulnerable population such as that of migrants living in informal settlements lose their jobs, they have to cope with loss of income, food shortages, family worries, and uncertainty about their future, [ 19 , 20 ] and this worsening of socio-economic conditions together with the loss of employment for low-income individuals increases the risk of developing psychiatric disorders, [ 21 ] such as psychological distress, depressive disorders, anxiety disorders, and substance use disorders. [ 22 ] Psychological distress refers to a range of nonspecific symptoms of stress, anxiety and depression that can trigger and act as signs of common mental disorders, such as depressive and anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…However, the association between conspiracy beliefs and mental health (i.e., the predictive value of mental health in this context) is not yet fully understood. Depressive symptoms [ 14 , 31 ] and stress [ 32 , 33 ], for example, were associated with greater endorsement of conspiracy beliefs during the pandemic. Before the pandemic, research on mental health and its connection to conspiracy beliefs was relatively sparse: one report found that perceived stress and trait anxiety had small effects on beliefs [ 34 ], while others focused on the predictive value of clinical or maladaptive personality traits, such as schizotypy and negative affectivity (e.g., [ 35 ]).…”
Section: Introductionmentioning
confidence: 99%